Consumer Preferences: Exploring Brand Awareness, Product Variation, and Purchase Intentions in Purchase Decisions - Navanti, Dovina; Giningroem, Dewi Sri Woelandari Pantjolo; Indra, Christophorus; Setyawati, Novita Wahyu (Majalah Ilmiah Bijak, 2024)
This research aims to explore the impact of brand awareness and product variety on purchasing decisions for Lemonilo noodles in Bekasi through purchase intention. The method we use is a quantitative method, where we use a purposive sampling technique to select 128 respondents who are consumers of Lemonilo noodles in Bekasi City. The results show that the second factor, brand awareness and product variety, influences purchase intention, but only product variety has a significant impact on purchasing decisions. In addition, purchase interest acts as a reflection between brand awareness and product variety and purchasing decisions